PECULIARITIES OF TREATMENT OF RECURRENT BRONCHITIS IN FREQUENTLY AILING CHILDREN WITH FUNGAL AND BACTERIAL COLONIZATION OF NASOPHARYNX - T.G. Malanicheva; N.V. Ziatdinova; L.F. Akhmadieva ("Paediatrician" Publishers LLC, 2009)
90 frequently ailing children (FAC) under the age 3-7 years old with recurrent bronchitis were observed. In 53 (59%) of them a colonization of mucous tunica with Candida and Staphylococcus aureus was revealed. The complex treatment of bronchitis in 33 children included fusafungine (Bioparox), having high activity against S. aureus and Candida (4 nasal and 4 oral inhalations 4 times daily during 7-10 days). The control group contained 20 children, receiving traditional treatment. It was shown that complex treatment with fusafungine is effective in 79% of cases. The duration of exacerbation was decreased 1,8 times lower and the remission was prolonged two times longer on the basis of negative results of cultural mycological and bacteriological tests. Described complex treatment with fusafungine can be widely used in FAC with recurrent bronchitis, associated Candida and S. aureus. Key words: frequently ailing children, recurrent bronchitis, Сandida, Staphylococcus aureus, fusafungine. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(6):97-100)